Article 20 of the Unesco convention on cultural diversity: its use for promoting respect for cultural diversity in WTO Law - Barreiro Carril, Beatriz (CUADERNOS DE DERECHO TRANSNACIONAL, 2014)
Abstract: This article deals with the “conflict clause” in the UNESCO Convention for the Promotion and Protection of the Diversity of Cultural Expressions. The relationship to WTO Law is clear, since one of the purposes of this Convention is to reaffirm the States’ “sovereign right to formulate and implement their cultural policies and to adopt measures to protect and promote the diversity of cultural expressions and to strengthen international cooperation to achieve the purposes of [the Convention] (art. 5.1) which are, among others, to give “recognition to the distinctive nature of cultural ...goods and services as vehicles of identity, values and meaning” (art. 1.(g)). The commerce of such goods and services is the object of WTO Law. In order to reaffirm the cultural sovereignty of States, the Convention refers to possible measures that States may adopt, such as “regulatory measures aimed at protecting and promoting diversity of cultural expressions” (art. 6.2.(a)). Among these measures are the well-known quotas reserving a space for domestic audiovisual products, which would normally breach the general principles of WTO Law. This article explores how the “conflict clause” set out in Article 20 of the UNESCO Convention may be successfully invoked, and where that is the case, whether the UNESCO Convention would be the applicable law. Since there is no precedent yet for successfully invoking Article 20 to apply the UNESCO Convention instead of, or as a complement to, WTO Law, this article speculates on some options opened up by interpreting international law in a way that is favourable to cultural diversity claims. Key words: UNESCO Convention for the protection and promotion of the diversity of cultural expressions; WTO Law, Cultural Products, Audiovisual sector, “conflict clauses” in International Treaties, conflicts of treaties in International Law, Interpretation of Treaties. Resumen: Este artículo se centra la cláusula de solución de conflictos entre tratados contenida en la Convención de la UNESCO para la protección y la promoción de la diversidad de expresiones culturales. La relación con el Derecho de la OMC es clara, ya que uno de los objetivos de la Convención es reafirmar el derecho soberano de los Estados para implementar sus propias políticas culturales de apoyo a sus productos culturales. El principal foro donde se negocia el comercio de tales productos es la propia OMC. Este artículo explora como el artículo 20 de la Convención de la UNESCO puede ser invocado con éxito para favorecer la aplicación de la Convención. Dado que no hay un precedente similar, este artículo considera algunas opciones que la interpretación del Derecho Internacional permite para obtener un resultado favorable a las demandas de la diversidad cultural. Palabras clave: Convención de la UNESCO para la protección y la promoción de la diversidad de las expresiones culturales; Derecho de la OMC; productos culturales, sector audiovisual; normas de solución de conflictos contenidas en tratados internacionales, conflictos entre tratados en Derecho Internacional, Interpretación de Tratados.